2009
DOI: 10.1021/ja9024879
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonamido−Phosphoramidite Ligands in Cooperative Dinuclear Hydrogenation Catalysis

Abstract: Sulfonamido-phosphoramidite ligands lead to the formation of Rh-Rh dinuclear complexes through the anionic P-N(-) bridging character. The resulting "boat-shaped" dinuclear catalysts activate molecular H(2) through a cooperative dinuclear endocyclic mechanism, resulting in one bridging and one classical hydride on the dinuclear complex. These new complexes are very active hydrogenation catalysts that operate via a new cooperative hydrogenation activation mechanism, as calculated with density functional theory, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 36 publications
0
49
0
4
Order By: Relevance
“…S1 and S2 are frequently used benchmark substrates in the asymmetric hydrogenation reaction, however, S3 is a relatively difficult substrate to hydrogenate and only few systems are reported that provide high enantioselectivity for this substrate. [18] The reaction mixtures were prepared in situ by addition of solvent (CH 2 Cl 2 ) to a mixture of the appropriate amounts of metal precursor, ligand and substrate. Next, the reaction mixtures were put under an atmosphere of dihydrogen.…”
Section: Resultsmentioning
confidence: 99%
“…S1 and S2 are frequently used benchmark substrates in the asymmetric hydrogenation reaction, however, S3 is a relatively difficult substrate to hydrogenate and only few systems are reported that provide high enantioselectivity for this substrate. [18] The reaction mixtures were prepared in situ by addition of solvent (CH 2 Cl 2 ) to a mixture of the appropriate amounts of metal precursor, ligand and substrate. Next, the reaction mixtures were put under an atmosphere of dihydrogen.…”
Section: Resultsmentioning
confidence: 99%
“…It remains to be seen if the amino linker of ligand 20, like its CH 2 analogues, will be available for cooperative catalysis (as observed for the METAMORPhos type sulfonamidophosphoramidites [7,8] ). This reaction would, in principle, offer new possibilities for this versatile subclass of tridentate PNP ligands.…”
Section: Ironmentioning
confidence: 99%
“…[7,8] These developments in turn allow a wider range of activity than that traditionally provided by metal-based catalysis alone.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Diese Entwicklungen könn-ten die Möglichkeiten üblicher metallkatalysierter Reaktionen erweitern.…”
Section: Einführungunclassified
“…Es bleibt abzuwarten, ob die Aminogruppe, die im Ligand 20 als Brücke vorliegt, wie die CH 2 -Gruppen in analogen Liganden für die kooperative Katalyse zur Verfügung steht (wie bei Sulfonamido-Phosphoramiditen vom MetamorphosTyp [7,8] ). Somit würden sich neue Möglichkeiten für diese vielseitige Klasse dreizähniger PNP-Liganden ergeben.…”
Section: Eisenunclassified